Institutional Readiness in Implementing Semarang Mayor Regulation No. 79 of 2020 Concerning the Implementation of Early Children's Education 1 (One) Year of Pre-Primary School - Neneng Tasu’ah; Shinta Okti Puspitasari (Universitas Negeri Semarang, 2024)
This research aims to determine the readiness of institutions to implement Semarang Mayor Regulation no. 79 of 2020 and to find out supporting and inhibiting factors in implementing these regulations. The approach in this research uses a qualitative method with a qualitative descriptive research type. Data collection techniques in this research are observation, interviews and documentation. Research analysis techniques include data reduction, data presentation and drawing conclusions. Based on the results of interviews based on 8 scopes of Semarang Mayor Regulation no. 79 of 2020 that the institution has prepared and implemented the Regulations well. First, the Pedurungan State Kindergarten is ready in all aspects. Secondly, the strongest aspect of ABA 42 Kindergarten that has been prepared by the institution is in terms of the curriculum aspect using an independent curriculum based on loose part learning, while the weakest aspect is in the teaching staff aspect, where out of 5 teaching staff, 3 teaching staff do not have a Bachelor's degree in PAUD or a Bachelor's degree in Psychology. . Third, in Sultan Agung 02 Kindergarten, the strongest aspect that the institution has prepared is financing, while the weakest aspect is the teaching staff and educational staff. The four Kebon Dalem 02 Kindergartens, the strongest aspect that has been prepared, is community participation, and the weakest aspect is the teaching staff and education staff, whereas if seen as a whole, looking at the 8 scopes, the most prepared aspect is financing and the least prepared aspect are educators and educational staff. Supporting factors for institutional readiness in implementing Semarang Mayor Regulation no. 79 of 2020, namely that all parties, namely teachers, parents and the community around the institution support the existence of policies and the implementation of these regulations. The inhibiting factor is that there are still many parents who do not understand and understand the importance of early childhood education and whether children with special needs in institutions can implement the 1 (one) year PAUD program or not.